Time-lapse analysis of sparse 3D seismic data from the CO2 storage pilot site at Ketzin, Germany - Ivandic, M.; Yang, C.; Lüth, S.; Cosma, C.; Juhlin, Christopher (2012)
The Ketzin pilot site is the first European on-shore CO2 storage project site. Injection started in June 2008 and until the latest repeat survey in February 2011 around 45,000t of CO2 had been injected into a saline aquifer at approximately 630m depth. Seismic monitoring methods that have been applied at the Ketzin site comprise baseline and repeat observations at various scales. We present here time-lapse results from sparse 3D seismic data measurements at Ketzin, which were acquired to link downhole surveys with conventional 3D surface seismic surveys. The results are consistent with the 3D seismic time-lapse studies over the injection site and show that the sparse 3D geometry can be used to map the CO2 in the reservoir at a significantly lower effort than the conventional 3D surveying. The last repeat survey indicates preferential migration of the CO2 to the west. There are no indications of migration into the caprock on either of the repeat surveys. © 2012 Elsevier B.V.